“WAITING FOR GODOT”: A PHILOSOPHICAL PLAY BY SAMUEL BECKETT - Shukurova Zamira (Bright Mind Publishing, 2025)
This article explores Samuel Beckett’s Waiting for Godot as a significant philosophical play within the Theatre of the Absurd. It examines the themes of absurdism, existentialism, and the human condition, analyzing the play’s portrayal of meaninglessness and human suffering. The study connects Beckett’s work with the ideas of Albert Camus, Jean-Paul Sartre, and Martin Heidegger. Additionally, it discusses the play’s structural and stylistic elements, its religious and political interpretations, and its enduring relevance in modern philosophical discourse.
Keywords: Absurdism, existentialism, Samuel Beckett, Waiting for Godot, philosophy, Theatre of the Absurd, nihilism, human condition, meaning of life, fate, free will, post-war literature.